Faktor-faktor Penentu Keberhasilan Pelepasliaran Elang Bondol (Haliastur indus Boddaert, 1783) di Taman Nasional Kepulauan Seribu - Nurul ulumiyah (Graduate School Bogor Agricultural University (SPs IPB), 2019)
A population of the brahminy kite in Java has threatened and decreased drastically. One effort to maintain the population is releasing brahminy kite in their natural habitat. The determinants of successful release were affected by reintroduction preparatory activities, rehabilitation, and post-release. The aims of this research were to analyze the management of release preparations and to formulate a model of a successful release. The research took a place in Kepulauan Seribu National Park on August-September 2017. Collection of preparatory release data and rehabilitation activities used direct observation and interviews, observation of behavior in rehabilitation cage used animal focal sampling method, and the post-release activity observation used Point Count method.The success of rehabilitation and post-release of the brahminy kite was analyzed using principal component analysis (PCA). The result showed that the management of cages, feed, care and treatment, health, staff, and facilities which affected the success of the release preparation. Successful of release models were influenced by successful rehabilitation and post-release. The benchmark of release behavior influenced by hunting and flying behavior. While the most dominant success of post-release the brahminy kite was influenced by tree height, a wide area of release habitat and the number of individuals released.